Variation in dental services by rurality among privately insured adults in the United States. (12th September 2020) - Simon, Lisa; Ahern, John; Fox, Kathe; Barrow, Jane; Palmer, Nathan
Abstract: Objectives: Rurality is associated with reduced dental access and worse oral health outcomes. It is unknown whether there is variation in dental services received by rural adults who visit a dentist. Methods: This was a retrospective analysis of claims data from a large private insurer. All individuals who had at least one dental visit in 2018 were included. Patient demographics, whether or not a patient's ZIP code was rural as defined by the Federal Office of Rural Health Policy, as well as ZIP code demographics were collected. Differences in the frequency of dental services received were evaluated using χ 2 tests. Multilevel logistic regressions were used to evaluate the individual and ZIP code‐level correlates of receiving a preventive dental procedure, a tooth extraction, or a denture‐related dental procedure. Results: Rates of preventive, oral and maxillofacial surgery, and denture‐related procedures were higher among rural adults. Accounting for individual age and gender, and ZIP code average income and dentist density, rural dwellers were more likely to receive a preventive procedure [odds ratio (OR) 1.15, P < 0.0001] or tooth extraction (OR 1.08, P < 0.0001), and less likely to have a denture‐related procedure (OR 0.94, P = 0.015) compared to nonrural dwellers. Female gender was the strongest predictor of receiving a preventive procedure (OR 1.30, P < 0.0001). Conclusions: Even among privately insured individuals with known access to dental care, rurality was associated with significant differences in the frequency of various dental procedures. Rural dental patients may have higher needs for oral surgical procedures, even when they have access to preventive care.